2015
DOI: 10.1371/journal.pgen.1005498
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Association Study of a Biomarker of Nicotine Metabolism

Abstract: Individuals with fast nicotine metabolism typically smoke more and thus have a greater risk for smoking-induced diseases. Further, the efficacy of smoking cessation pharmacotherapy is dependent on the rate of nicotine metabolism. Our objective was to use nicotine metabolite ratio (NMR), an established biomarker of nicotine metabolism rate, in a genome-wide association study (GWAS) to identify novel genetic variants influencing nicotine metabolism. A heritability estimate of 0.81 (95% CI 0.70–0.88) was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
158
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 111 publications
(173 citation statements)
references
References 72 publications
15
158
0
Order By: Relevance
“…Importantly, loci in the 19q13 region were previously implicated in quantity smoked by the TAG Consortium in their combined analysis and also by the ENGAGE 11 analysis and, recently, by Loukola et al 41 ; the region has been proposed as a plausible candidate for further investigation in relation to smoking quantity given its role in nicotine metabolism (see e.g., 13 ). We now add age at initiation to the list of smoking phenotypes to be further investigated in relation to this biologically plausible region.…”
Section: Discussionmentioning
confidence: 96%
“…Importantly, loci in the 19q13 region were previously implicated in quantity smoked by the TAG Consortium in their combined analysis and also by the ENGAGE 11 analysis and, recently, by Loukola et al 41 ; the region has been proposed as a plausible candidate for further investigation in relation to smoking quantity given its role in nicotine metabolism (see e.g., 13 ). We now add age at initiation to the list of smoking phenotypes to be further investigated in relation to this biologically plausible region.…”
Section: Discussionmentioning
confidence: 96%
“…Smokers with faster rates of nicotine metabolism, as determined by the NMR, have higher quit rates on varenicline versus the nicotine patch; in contrast, varenicline is not superior to the patch in slower metabolizers [22] (Figure 2). NMR genome-wide association studies have identified novel sources of genetic variation in CYP2A6 activity which may improve the optimization of treatment using CYP2A6 genomics and phenotype (NMR) in the future [78]. Future studies should aim to determine a) the optimal NMR cut-point for distinguishing between faster and slower metabolizers (see Outstanding Questions), and b) whether the utility of NMR, as opposed to using a purely genetics-based approach, may be limited by transient environmental influences.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published GWAS found 3 variants (rs56113850, rs113288603, and esv2663194) to be globally associated with nicotine metabolism (49). Of these, in our study, only rs56113850 was strongly associated with both CYP2A6 activity levels and lung cancer risk, while rs113288603 and esv2663194 ( CYP2A6 *12 ) were also associated with CYP2A6 activity, but were not strongly associated with lung cancer.…”
Section: Discussionmentioning
confidence: 99%